Two- and three-phase equilibria in polydisperse Yukawa hard-sphere mixture. High temperature and mean spherical approximations - Hvozd, T.V.; Kalyuzhnyi, Y.V. (Condensed Matter Physics, 2016)
Phase behavior of the Yukawa hard-sphere polydisperse mixture with high degree of polydispersity is studied using high temperature approximation (HTA) and mean spherical approximation (MSA). We have extended and applied the scheme developed to calculate the phase diagrams of polydisperse mixtures described by the truncatable free energy models, i.e., the models with Helmholtz free energy defined by the finite number of the moments of the species distribution function. At high degree of polydispersity, several new features in the topology of the two-phase diagram have been observed: the cloud and shadow curves intersect twice and each of them forms a closed loop of the ellipsoidal-like shape with the liquid and gas branches of the cloud curve almost coinciding. Approaching a certain limiting value of the polydispersity index, the cloud and shadow curves shrink and disappear. Beyond this limiting value, polydispersity induces the appearance of the three-phase equilibrium at lower temperatures. We present and analyze corresponding phase diagrams together with distribution functions of three coexisting phases. In general, good agreement was observed between predictions of the two different theoretical methods, i.e., HTA and MSA. Our results confirm qualitative predictions for the three-phase coexistence obtained earlier within the framework of the van der Waals approach.